Impacts of the 2018 M7.1 Anchorage earthquake on schools. Issue 3 (August 2021) - Rodgers, Janise; Hassan, Wael; Motter, Christopher; Thornley, John
The 2018 M7.1 Anchorage earthquake damaged over 120 schools in the Anchorage and Matanuska-Susitna (Mat-Su) School Districts. Many remained closed for a week or more for cleanup and repairs, primarily due to nonstructural damage. Major structural damage occurred in three of 132 school buildings across both districts, and a number of additional schools had minor to moderate damage. Most observed damage was to nonstructural components, including suspended ceilings, lighting, architectural finishes, building utility systems, and equipment. Middle and high schools were in session at the time of the earthquake. Despite ceiling damage and fallen ceiling tiles, books, and supplies (heavy furniture was anchored) and objects swinging from the ceiling, both districts reported very few injuries. Statements by the school districts and administrators, media reports, and available video indicate that most students dropped, covered, and held on as practiced in regular drills. The combination of life-safety structural performance (with a few exceptions) due in part to moderate shaking, as well as anchoring of heavy furnishings, and student preparedness and drills to practice protective action, appears to have protected students. Both districts' experiences provide evidence that school seismic safety programs are valuable, even if efforts to mitigate risks from older, vulnerable schools are in process and more work remains.